THE INFLUENCE OF COMPENSATION, ORGANIZATIONAL COMMITMENT AND CAREER PATH TO JOB PERFORMANCE EMPLOYEES - Triana, Yuli (Jurnal Aplikasi Manajemen, 2017)
This study aimed to analyze the influence of Compensation, Organizational Commitment and Career Path to Job Performance Employees at the College of Economics in Banjarmasin South Kalimantan Indonesia. Either simultaneously or partially and the dominant variable affecting work achievement by the number of respondents was 35 people. Data were collected through questionnaires, interviews and direct observation to the object of research. The object of research conducted at the School of Economics Indonesia in Banjarmasin. Data collection techniques using explanatory Research by highlighting the influence of variables. This research included in the quantitative research. Data analysis techniques using multiple linear regression. The results showed that simultaneous Compensation, Organizational Commitment, and Career have a significant effect on the achievement of Employees at the Open University UPBJJ Banjarmasin, while the partial effect of all the variables also has an influence on work performance. The dominant variable affecting work performance is variable compensation with a significant level of 0.0000.